Foreign Exchange Transactions (Sharf) in the Perspective of Fiqh Muamalah: Between Classical Traditions and the Challenges of the Contemporary Global Economy - Syaripuddin, Syaripuddin; Sunarta, Desy Arum; Mashuri, Arif; Mulyawan, Andi Wawan; Khaeriyah, Hamzah; Wijaya, Abdi (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
The rapid development of the global economy has increased the need for foreign exchange (Sharf) transactions across individuals, financial institutions, and nations. However, concerns about the permissibility of foreign exchange transactions from the perspective of Islamic law (fiqh muamalah) have become increasingly relevant. This study examines the sharia principles governing Sharf transactions, focusing on the application of fiqh muamalah to both classical and contemporary foreign exchange practices, particularly those involving digital technology. The research employs a descriptive qualitative method through a literature-based approach, exploring the views of classical and contemporary scholars, and analyzing the role of fatwas in ensuring compliance with sharia principles. The findings reveal that foreign exchange transactions must fulfill requirements such as immediate mutual exchange (taqabudh fi al-majlis) and avoid elements of usury (riba), uncertainty (gharar), and gambling (maysir). In the digital era, new challenges have emerged with the rise of financial instruments such as forex margin trading and cryptocurrency, requiring adaptive legal interpretations within the framework of fiqh muamalah to maintain sharia compliance. Thus, contemporary ijtihad and fatwas from sharia financial authorities are essential in guiding technology-based foreign exchange transactions to remain within Islamic legal boundaries.